VDC_100102371237.0X000001. Issue 10 (October 2018) - Manguso, Nicholas; Gangi, Alexandra; Nissen, Nicholas; Harit, Attiya; Siegel, Emily; Hendifar, Andrew; Amersi, Farin
Small bowel neuroendocrine tumors (SBNETs) are often indolent, but occasionally, patients present with acute symptoms requiring emergent operative intervention. Our aim was to determine whether emergency surgery for SBNETs affects long-term outcomes. An institutional database was reviewed to identify patients with SBNET diagnosed between 1990 and 2015. Need for emergency resection (ER) was compared with elective resection (ELR). One hundred and thirty-four patients met inclusion criteria. Median age was 59 years (range, 21–91), and median tumor size was 1.5 cm (range, 0.1–5). Median follow-up time was 5.5 years. One hundred (74.6%) patients had ELR, whereas 34 (25.4%) required ER. ELR had a higher number of lymph nodes resected (median 12.5 vs 8 ER, P = 0.04); however, there was no difference in the number of positive nodes (median 3 vs 2, P = 0.85). There were 45 (33.6%) recurrences (31 [31.0%] ELR vs 14 [41.7%] ER, P = 0.29) and 13 (9.7%) deaths (7 [7.0%] ELR; 6 [17.6%] ER). There was no significant difference in 5-year disease-free survival (ELR 72.6% vs ER 77.9%, P = 0.71) or overall survival (ELR 97.2% vs ER 96.6%, P = 0.81). Although patients undergoing ER have significantly fewer lymph nodes resected, they have comparable recurrence rates and long-term outcomes with those patients undergoing ER.